Spatial variation in high temperature‐regulated gene expression predicts evolution of plasticity with climate change in the scarlet monkeyflower. Issue 4 (12th December 2021) - Preston, Jill C.; Wooliver, Rachel; Driscoll, Heather; Coughlin, Aeran; Sheth, Seema N.
Abstract: A major way that organisms can adapt to changing environmental conditions is by evolving increased or decreased phenotypic plasticity. In the face of current global warming, more attention is being paid to the role of plasticity in maintaining fitness as abiotic conditions change over time. However, given that temporal data can be challenging to acquire, a major question is whether evolution in plasticity across space can predict adaptive plasticity across time. In growth chambers simulating two thermal regimes, we generated transcriptome data for western North American scarlet monkeyflowers ( Mimulus cardinalis ) collected from different latitudes and years (2010 and 2017) to test hypotheses about how plasticity in gene expression is responding to increases in temperature, and if this pattern is consistent across time and space. Supporting the genetic compensation hypothesis, individuals whose progenitors were collected from the warmer‐origin northern 2017 descendant cohort showed lower thermal plasticity in gene expression than their cooler‐origin northern 2010 ancestors. This was largely due to a change in response at the warmer (40°C) rather than cooler (20°C) treatment. A similar pattern of reduced plasticity, largely due to a change in response at 40°C, was also found for the cooler‐origin northern versus the warmer‐origin southern population from 2017. Our results demonstrate that reduced phenotypic plasticity can evolve with warming and that spatial and temporal changes in plasticity predict one another.